PENGARUH PENGGUNAAN MEDIA FILM ANIMASI TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN FIQIH KELAS IX MTS MIFTAHUL ULUM SETU BEKASI - Junia Rahmawati; Yayat Suharyat (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2021)
Background This study examines Fiqh learning about the practice of mu’amalah (buying andselling) by using learning media in the form of animated film media. This teaching and learning activitywill definitely lead to a different and fun learning situation, it will also create and build an activerelationship between educators and students so that learning outcomes are high. The formulation ofthe research problem isIs there any effect of using animated film media on student learning outcomes inFiqh subjects at MTS Miftahul Ulum Setu Bekasi. This study aims to determine and analyze the effectof using animated film media on student learning outcomes in Fiqh subjects at MTS Miftahul UlumSetu Bekasi. The research methodology used is Quasi Experiment. In the experimental class usingAnimated Film Media and the control class using the Discussion method. This research instrument usesPretest and Posttest. the population in this study were all students of class IX as many as 40 students.The research sample was 20 students for the experimental class and 20 students for the control class.The results of the experimental class research are obtained average pretest 62.50 and the averageposttest result is 80.50. Then, the hypothesis was tested using the t-test, so that the Sig. (tailed-2) valuewas 0.004 with a significance level (α) <0.05, then H1 was accepted and H0 was rejected. The resultsof the study in the control class obtained an average pretest result of 59.00 and an average posttestresult of 71.25 then hypothesis testing was carried out using the t-test to obtain the Sig. (tailed-2) valueof 0.000 with a significance level of ( ) < 0.05 then H1 is accepted and H0 is rejected. Based on theseresults, it can be seen that student learning outcomes using animated film media in the experimentalclass are greater than those using the Discussion method in the control class.